‘It depends on who I'm with’: How young people with developmental language disorder describe their experiences of language and communication in school - Ekström, Anna; Sandgren, Olof; Sahlén, Birgitta; Samuelsson, Christina (International journal of language & communication disorders, 2023)
Background The risks of developmental language disorder (DLD) for both educational progress and socio‐emotional development are well documented, but little is known about how children and young people with DLD experience and describe their language and communication. The need to complement experimental and quantitative studies with qualitative perspectives of the lived experience of individuals with DLD for speech and language therapists (SLT) practice has recently been foregrounded. Aims To understand further the experiences of young people with DLD focusing on language and communication in a school context, and thereby contribute to the improvement of the communicative situation in school for this group. The study is guided by the following research question: How do young people diagnosed with DLD describe their experiences of language and communication in school? Methods & Procedures The study is based on data generated from qualitative semi‐structured interviews with 23 participants diagnosed with DLD (age 13–19 years old) living in Sweden. All participants attended mainstream schools. To enable data to be collected during COVID‐19 restrictions, all interviews were conducted using Zoom. Reflexive thematic analysis was used to analyse the data. Outcomes & Results Four main themes related to experiences of language and communication in school were constructed from the interviews: (1) feelings of inadequacy and comparisons with others; (2) feelings of being misjudged and misunderstood; (3) the importance of feeling safe and comfortable; and (4) the significance of the social and communicative context. The results bear witness of difficult and challenging aspects related to language and communication in school, including educational, social and emotional dimensions. An important outcome of this study is how young people diagnosed with DLD describe their language and communication functioning to be dependent on both individual characteristics and abilities, as well as situational, contextual and social factors. Conclusions & Implications The results from this study show that young people with DLD can have persisting problems related to language and communication in school, including educational, social and emotional dimensions. SLT services may therefore be needed throughout the school years to ensure that students with DLD receive adequate support. In addition, support that goes beyond language abilities and targets social, contextual and emotional aspects should be considered. WHAT THIS PAPER ADDS What is already known on this subject Children and young people have unique knowledge about their language and communication which is instrumental for designing interventions and support strategies. Qualitative analyses of interview data have been able to identify both risk factors and protective strategies in relation to the well‐being of individuals with DLD. Despite this, children and young people with DLD are rarely heard in research or clinical discussions. What this paper adds to existing knowledge In this study we listen to the voices of young people with DLD as they describe their experiences of language and communication in school. The participants describe a condition that makes them struggle to keep up with peers and puts them at risk of being misjudged by teachers, but also give examples of situations where negative consequences are hardly felt. What are the potential or actual clinical implications of this work? DLD is a complex and dynamic disorder where contextual and social factors interact with individual abilities in creating the end result. The results of the study indicate that DLD can cause persisting problems related to language and communication in school, with impact on educational, social and emotional dimensions. To counteract these effects, SLT services may be needed throughout the school years, and support that goes beyond language abilities must be considered.